Collaborative Learning as the Basis for the Development of Foreign Language Communicative Competence - Inagamova Umida Rustamovna (International Journal on Integrated Education, 2022)
It is known that world has never experienced so many changes as in the XXI century. There is a restructuring of not only the population of the planet itself, but also changes in various areas, such as economic, social, political, cultural and others. In addition, today, in all countries of the world, much attention is paid to the education system. The modern education system requires constant updating and improvement, due to the reorientation of education at the state level, the rapid development of information technology, the latest technical devices. The article deals with the theory of collaborative learning and its role in developing foreign language communicative competence.